Work Under the Façade of Mainstream Discourse : Defining Work with George Orwell, Hannah Arendt, Bertrand Russell and David Graeber - Mustakoski, Kai (My University, 2021)
In this thesis I analyze how work is defined by George Orwell, Hannah Arendt, Bertrand Russell and David Graeber in their texts selected for this thesis. Work is commonly thought with certain assumptions that seem common-sense to most people. I argue that it is impossible to talk about work in a meaningful way if it is not first defined with full acknowledgment of the ideological background against with it is described. Overall, this study simply concentrates how the word work can be defined. The study focuses on the term work as a social phenomenon (i.e. a ritual performed) by analyzing the aforementioned four prominent thinkers’ writings. I investigate these text in order to develop ideas of work that delve into the aspect beyond those of common perception. In four case studies, I analyze some writings by George Orwell, Hannah Arendt, Bertram Russell and David Graeber for the purpose of conjuring an image of work as a social construct that appears to have a strong sense of morality, duty and sacrifice that has been implemented top down in an attempt of controlling societies and status quo. I claim that the discussion on work is largely neglected in academia and in mainstream discourse, especially in the sense what work actually entails as a means of maintain the order of society today. I argue that work is one of the most defining aspect of human beings in societies: consumes most of the time of human lifespan, physiologically uses a great deal energy (also mental), causes a lot of serious health problems, defines people’s lives for them without no real freedom in choosing one’s profession (dictated ultimately by necessity). My study illustrates that while work is been talked about at every turn, it is seldom talk about what it actually entails as a social practice and under the various beliefs and assumptions attached to it. Therefore, I argue that a lot of time work is been talked about, it is not at all clear what is actually meant by it, thus making the discourse stuck in a certain parameters set by the current market logic and its definition of value(/money).
Keywords: Work, Labor, Value, Society, Class, Time